Relationship between Euthyroidism and Muscle Mass and Strength: A Systematic Review - Greco, Francesca; Moulton, Chantalle; Antinozzi, Cristina; Lista, Marco; Di Luigi, Luigi; Dimauro, Ivan; Sgrò, Paolo (International Journal of Sports Medicine, 2023)
Thyroid hormones play a crucial role in skeletal muscle development, suggesting that thyroid function may influence muscle mass and muscle strength, which are both fundamental health-related indicators of several age-related consequences. However, whether there is a relationship between thyroid hormones, muscle mass, and muscle strength in individuals without thyroid dysfunctions is still unknown. Therefore, this systematic review aims to investigate whether thyroid hormones are related to muscle mass and strength parameters in euthyroid individuals. Three databases were searched (PubMed, Scopus, Web of Science) up to February 14, 2022, for peer-reviewed papers published in English. The search results were conducted independently by two different reviewers. The review included 13 studies with a total of 241,044 participants. All studies were observational: twelve studies measured thyroid stimulating hormone, ten and thirteen studies measured free triiodothyronine and free thyroxine, four studies analyzed the thyroid hormone ratio. The assessment methods for muscle mass were computed tomography, dual-energy X-ray absorptiometry and bioimpedance analysis, whereas hand dynamometer for muscle strength. Low levels within the normal range of free triiodothyronine, high levels within the normal range of free thyroxine, and lower thyroid hormone ratio may contribute to a reduced muscle function, which seems more evident in older males.
Keywords: exercise; skeletal muscle; aging; thyroid; health; exercise; endocrinology; health; sport; doping; skeletal muscle; ageing; bone mineral density; physical exercise